Circadian exosomal expression of renal thiazide‐sensitive NaCl cotransporter (NCC) and prostasin in healthy individuals. Issue 5 (June 2015) - Castagna, Annalisa; Pizzolo, Francesca; Chiecchi, Laura; Morandini, Francesca; Channavajjhala, Sarath Kiran; Guarini, Patrizia; Salvagno, Gianluca; Olivieri, Oliviero; Capelo Martínez, José Luis; Lodeiro, Carlos; Santos, Hugo M.
<x xml:space="preserve">Abstract</x> Purpose A circadian timing system is involved in the maintenance of fluid and electrolyte balance and blood pressure control. Aldosterone and vasopressin modulate ion transporters and channels crucial in sodium (Na) and water reabsorption such as the epithelium Na channel and the renal thiazide‐sensitive NaCl cotransporter (NCC). We analyzed in urinary exosomes the intraday variations of NCC and prostasin expression and the association with electrolytes and water balance parameters. Experimental design Blood and urine samples were collected at five time points during the day from five healthy subjects. Blood renin, aldosterone, cortisol, ACTH, and plasmatic and urinary Na, potassium, creatinine, adiuretin (ADH), NCC, and prostasin were evaluated. Results ACTH and cortisol showed a circadian pattern, similarly to aldosterone, while exosomal NCC and prostasin pattern were similar to urinary ADH, decreased in the morning and subsequently increased in the afternoon and evening. Conclusions and clinical relevance In urinary exosomes, NCC and prostasin had a diurnal pattern parallel to ADH and aquaporin 2, confirming that, in healthy subjects, both prostasin and NCC relate to water balance. These results provide suggestions for a possible chronotherapeutic approach in patients treated with thiazides, diuretic drugs acting as specific inhibitors of NCC‐mediated Na reabsorption.